Polymorphisms within Genes Coding for IL-17A and F and Their Receptor as Clinical Hallmarks in Ankylosing Spondylitis - Joanna Wielińska; Jerzy Świerkot; Katarzyna Kolossa; Bartosz Bugaj; Monika Chaszczewska-Markowska; Sławomir Jeka; Katarzyna Bogunia-Kubik (Mediators of Inflammation)
IL-17A and IL-17F together with their coreceptor (IL-17RA/RC) were reported to play a significant role in the pathogenesis of spondyloarthritis. The group of axial spondyloarthritis comprises ankylosing spondylitis (AS), a rheumatic disease characterized by chronic inflammation of the joints in the spine. This study is aimed at investigating IL-17A, IL-17F, IL-17RA, and IL-17RC polymorphisms as potential biomarkers of disease susceptibility, clinical parameters, and anti-TNF treatment outcome in a cohort of Polish ankylosing spondylitis patients. In total, 328 subjects, including 138 AS patients and 190 healthy volunteers, participated in the study. Genotyping of IL-17A rs2275913 (G/A), IL-17F rs763780 (A/G), IL-17RA rs4819554 (A/G), and IL-17RC rs708567 (G/A) was performed on real-time PCR instrument using LightSNiP assays. No significant differences were revealed in genotype and allele distribution between patients and controls despite the association of the IL-17RC rs708567 AA homozygosity with the earlier onset of the disease. Moreover, some relationships between IL-17F rs763780 and IL-17RA rs4819554 polymorphisms with clinical parameters related to the disease activity and anti-TNF treatment outcome were observed. IL-17F rs763780 G allele was found to be associated with high disease activity and BASDAI after 6 months and poor response to the treatment while higher VAS values were more common among IL-17RA rs4819554 G variant carriers. In conclusion, the IL-17F rs763780 polymorphism should be considered as a promising biomarker of disease activity and anti-TNF treatment outcome. The IL-17RA rs48419554 G allele may serve as a potential marker of disease severity in Polish AS patients.